Microflora periodontal (1996)
ABSTRACT: Longitudinal studies of patients with various forms of periodontal disease have indicated that the destruction occurs in relatively short periods of time, followed by prolonged ones of inactivity and they are associates with a to predominantly an specific microbiota, to each entity in particular, If periodontal breakdown takes place during short periods of time, at individual sites and with an associated specific flora, it is then, desirable that the dentist be able to detect these periods and sites of activity, to identify the predominant microorganisms, and to be able to predict what is happening, from the clinic, microbiological, and immunological pounts of view, this would provide the bases for a proper diagnosis, a rational treatment, and the prevention of disease.